EFEKTIVITAS KEBIJAKAN DAN KESELAMATAN WISATAWAN DALAM TRANSFORMASI MANAJEMEN PARIWISATA JAWA TENGAH - swanny widyaatmadja; Benita Eka Ariani; Albertus Setyo (JURNAL KEPARIWISATAAN, 2026)
This study analyzes the transformation of tourism management in Central Java by highlighting the institutional differences between Disporapar (Youth, Sports, and Tourism Office) and Disbudpar (Culture and Tourism Office), projecting the development of the tourism sector if placed under Disbudpar, and identifying the weaknesses of Central Java tourism sector in terms of policy and occupational safety and health (K3). A mixed-method approach was applied, with qualitative analysis for policy and K3, and quantitative analysis of tourist visits data from 2019–2024 (before and after COVID-19). The findings reveal that placing tourism under Disporapar reduces institutional focus, while integration with culture under Disbudpar has the potential to strengthen cultural-tourism synergy. Weaknesses of Central Java's tourism sector include limited institutional coordination, uneven safety infrastructure, and weak occupational safety regulations. Policy recommendations include institutional repositioning, strengthening international-based tourism safety standards, and improving human resources capacity. Keywords : tourism management, policy, tourism safety, Central Java